Models for Self-Assembly of Nanoscale Systems with Biomedical Applications - V. Messina, Paula; Rial, Ramon; M. Ruso, Juan (Current Pharmaceutical Design, 2016)
Background: Understanding the physicochemical basis and the different models of nanosystems is nowadays fundamental in a great number of scientific areas and industrial processes. Results: Here, we focus on nanosystems created by self-assembly, molecular or inorganic. The organization of single units at these scales is a challenging matter in light of the inherently small dimensions involved, the sensitivity of the system to small perturbations, and the problem of scaling up such a process for widespread use and implementation. Conclusion: This review examines the different self-assembly routes used to create nanostructures in both the equilibrium and non-equilibrium/dynamic systems and discusses their limits and applications. The connection to biomedicine and pharmaceutical design has been emphasized.
Keywords: electromagnetic properties